Emotional marketing concept: The new marketing shift in the Postmodern era - Rytel, Tomas (Business: Theory and Practice, 2010)
The paper provides key assumptions for the development of the new theory shift, emotional marketing, as a natural outcome of the postmodern (consumer) society conditioned by the increasing need for consuming symbolic senses. Symbolic features of exchange objects shape the needs of the contemporary consumer, having a greater impact on their choice on the market. Emotional exchange factors affected by the increasing culture of consuming symbols become the key attribute of exchange in the postmodern era, therefore formation of the emotional marketing concept becomes a relevant object of research in contemporary marketing management. The increasing significance of symbols (their meanings and senses) in the contemporary consumer society becomes the key consumption stimulating factor and forms a new ethos of consumption, which triggers development of new marketing shifts.